Financiamento interno de longo prazo - Fernando Nogueira da Costa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– Besides the introduction and the final conclusions, this Discussion Paper has four sections. The first presents the "state of art", that is, the current debate about the long-term financing of the neo-corporatist state capitalism in Brazil. Then it shows the personal and corporate wealth as potential funding sources. This is evaluated by what means the reallocation of capital required in the portfolios may be held. Finally, shows the future possibility of incorporating new sources of investment financing through the sovereign wealth fund and pension funds.
Keywords: G20; G21; G23; 330; finance; credit market; capital market